Analisis Pemilihan Perangkat Lunak Sistem Enterprise Resource Planning (ERP) Menggunakan Analytical Hierarchy Process (AHP): Studi Kasus pada PT Ciliandra Perkasa - Roni Kurniawan (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Enterprise Resource Planning (ERP) can be described as a concept for planning and managing organization resources to create value added for stakeholders. PT Ciliandra Perkasa as an agribusiness company realized the importance of ERP system to support their operational activities. Indeed, there are many problems on the ERP implementation. Therefore, it is needed to build a proper ERP system process to be implemented. This issue will be the research problem. Implementing a qualitative method, this research uses primary data and secondary data as samples. Tests and analysis use Analytical Hierarchical Process (AHP) which its results are expected to guide the management of PT Ciliandra Perkasa in selecting proper software of ERP application.